Penetrasi Sosial dalam Virtual Blind Date (E-Jurnal Medium, 2022)
The development of technology and the limitations of physical activity during the Covid-19 pandemic have forced everyone to find ways to stay connected with family, friends, and romantic relationships. In early 2021, there is a virtual blind date which is an opportunity for those who are looking for friends and affection during the pandemic. Virtual blind date is an activity organized by a community where every dating couple will be met in an online meeting application which has been divided into breakout rooms. Each individual will get 3-4 times a pair and each last 15-20 minutes. This study aims to explain the stages of developing a virtual blind date dating couple relationship in a limited duration. This study uses qualitative research methods using social penetration theory and CMC. The results of the study managed to collect 6 informants with an age range of 18-25 years. All of the informants went through the orientation stage and the affective exchange stage, but not all the informants and each partner went through the affective exchange stage and the stable exchange stage. In the virtual blind date, the stable exchange stage is characterized by social media exchanges between dating partners to provide opportunities for continuing deeper conversations. Each informant has a different level of depth and topic of conversation with each partner. In conversations through CMC, some of the informants and their partners felt they could be more open because they did not know each other's backgrounds and there was visual anonymity, thereby reducing the possibility of obtaining justification.